Fracture characteristics and damage prediction in flat steel beams under contact explosions. (May 2023) - Ichino, Hiroyoshi; Kayamori, Yoichi; Beppu, Masuhiro; Williamson, Eric B; Yoshii, Ken-ichi
Highlights: Damage and fracture of flat, mild-steel under contact charges are investigated. Flat steel is damaged internally by stress wave and then broken by blast pressure. Brittle fracture prevails over ductile fracture in observation of fracture surface. Prediction method of damage level of flat steel under contact explosion are developed. Abstract: Research to predict and mitigate local damage of steel elements subjected to contact and close-in explosion remains a topic of interest. In this study, the effects of charge mass, specimen geometry, and explosive charge position on the damage and fracture of flat, mild-steel specimens under contact charges are investigated. From macroscopic and microscopic observations of the fracture surfaces, rupture properties of the flat steel specimen under contact explosion are examined. Based on these observations, the rupture process of flat steel specimens under contact explosion is considered as follows: 1) the opposite surface of a blast -loaded specimen was damaged by spalling due to tensile stress wave, and 2) the rest of the cross-section of a specimen was stretched and ruptured by blast pressure into two pieces. On the microscopic fracture surface observed by a scanning electron microscope demonstrates cleavage, which is caused by brittle spalling and rupture. Their microscopic fracture surfaces are different based on charge positions, specimen thicknesses, and observation points. Furthermore, the effects of charge mass and specimen cross-section on damage to steel specimens under contact explosions are evaluated, and empirical equations to predict thickness limits are developed for spalling and rupture of flat, mild-steel specimens.